Speculations IV : speculative realism - Austin, Michael (Editor); Ennis, Paul J. (Editor); Gironi, Fabio, 1983-; Gokey, Thomas; Jackson, Robert (Punctum Books, 2013)
"With this special volume of Speculations, the editors wanted to challenge the contested term "speculative realism," offering scholars who have some involvement with it a space to voice their opinions of the network of ideas commonly associated with the name"--